PERLINDUNGAN HUKUM TERHADAP FINANCIAL TECHNOLOGY REWARD BASED CROWDFUNDING PADA PROYEK DARI INDUSTRI KREATIF (Studi pada Platfrom Kickstarter.com) - Recca Ayu Hapsari; Apri nisa; Agatha jessica Putri (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
Bank Indonesia stated that Financial Technology/Fintech is the result of a combination of technology and financial services. Platforms such as Kickstarter, Indiegogo, Lending Club, Rock et Hub are becoming increasingly popular for crowdfunding new products and services. The type of contribution that supporters make determines the difference between these platforms. Kickstarter supporters can see first hand the creative process and contribute to the project's success.Several community groups have also developed insights to make the most of internet facilities. The research method used a normative legal approach and an empirical approach. The data collection technique used in this research is library research. Legal protection for financial technology reward based crowdfunding in creative industry projects (Studies on the Kickstarter.com Platform) explains that Kickstarter has adopted a general policy regarding copyright in accordance with the Digital Millennium Copyright Act of 1998. Keywords: Financial Technology; Technology; Kickstarter.